EIB Working Paper 2020/08 - EIB Group Survey on Investment and Investment Finance A technical note on data quality (Volume 2020/8) - Harasztosi, Peter (2020)
Providing a technical analysis of the data quality of the EIB Investment Survey (EIBIS), this paper finds that the chosen sampling framework captures the business population of interest well and that there is little evidence of selection bias during fieldwork. This suggests that EIBIS is a reliable data source to study the corporate investment situation in the EU.